2017
DOI: 10.1021/acs.analchem.7b01094
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid LC-MS/MS Method for the Quantification of Cannabidiol, Cannabidivarin, Δ9-Tetrahydrocannabivarin, and Cannabigerol in Mouse Peripheral Tissues

Abstract: Cannabis has been known as a medicine for several thousand years across many cultures and its beneficial effects are mostly due to the presence of cannabinoids, unique natural products, whose pharmacology is going to gain increasing interest in the scientific community. The discovery of the main psychoactive constituent of Cannabis sativa L., Δ-tetrahydrocannabinol (Δ-THC), led to the identification of at least 100 additional phytocannabinoids, including cannabidiol (CBD), cannabidivarin (CBDV), Δ-tetrahydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Table presents the summary of all LC‐based analytical methods for the quantification of cannabinoids in various animal samples published during 2010–2019 . All those LC methods were HPLC‐based, and there has been no report on the use of UPLC for animal sample during this period.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
See 1 more Smart Citation
“…Table presents the summary of all LC‐based analytical methods for the quantification of cannabinoids in various animal samples published during 2010–2019 . All those LC methods were HPLC‐based, and there has been no report on the use of UPLC for animal sample during this period.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
“…This method was shown to be highly sensitive and selective for simultaneous determination of cannabinoids 3 , 9 , 10 , 12 and THC‐COOH‐glucuronide in rat whole blood. Earlier, an HPLC‐ ESI‐MS/MS method in negative ion mode on an ion trap TOF MS was employed for the simultaneous detection and quantification of CBD ( 3 ), CBDV ( 5 ), CBG ( 6 ) and THCV ( 14 ) in mouse peripheral tissue samples . This method was rapid, precise and accurate, and could be used as a fundamental tool for pharmacokinetic and pharmacodynamic studies on phytocannabinoids in tissues from different animal models.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Naturally Occurring Canmentioning
confidence: 99%
“…The mechanism by which fish oil increases the intestinal anti‐inflammatory effects requires more in‐depth investigations. Here, we explored the possibility that fish oil could increase the bioavailability of the two phytocannabinoids; however, our validated LC‐MS‐IT‐TOF analysis (Piscitelli et al, 2017) revealed that fish oil did not affect the level of either CBD or CBD both in the serum and in the colon. It should be noted that, for another phytocannabinoid, namely cannabidivarin, its colonic levels were not correlated with its ability to attenuate intestinal inflammation (Piscitelli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We acquired full‐scan MSn spectra of selected precursor ions by multiple reaction monitoring, extracted the chromatograms of the high‐resolution [M−H]− values and used the latter chromatograms for calibration and quantification. Phytocannabinoids were separated and detected as previously described (Piscitelli, Pagano, Lauritano, Izzo, & Di Marzo, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Fractions were obtained by eluting the column with 99:1, 90:10, and 50:50 (v/v) chloroform/methanol. The 99:1 fraction was used for CBD quantification by LC–MS‐IT‐TOF analysis as described previously (Piscitelli, Pagano, Lauritano, Izzo, & Di Marzo, 2017).…”
Section: Methodsmentioning
confidence: 99%